Eksistensi Media Pembelajaran Digital pada Sekolah Dasar - Irfa'i Alfian Mubaidilla (Yayasan Al-Afif, 2025)
There has been a significant increase in the adoption of technology in teaching and learning processes, driven both by technological advancements and urgent responses to crises such as the COVID-19 pandemic. However, disparities in infrastructure, teacher competencies, and unequal access to digital resources remain critical issues that demand further attention. Therefore, this study aims to examine in depth the evolution of digital learning media at the elementary school level in Indonesia over the past decade and to identify supporting and inhibiting factors as a foundation for future policy recommendations and educational practices. This research employs a qualitative approach through a Systematic Literature Review (SLR) method to explore the existence and development of digital learning media in Indonesian elementary schools over the last ten years. In general, the use of digital media in primary education has had a positive impact on both the learning process and outcomes. Whether in regular, inclusive, or thematic learning contexts, digital media has demonstrated its effectiveness in supporting the achievement of educational goals. Nevertheless, technology integration must be accompanied by well-planned strategies, adequate teacher training, and policies that foster a healthy and inclusive digital learning ecosystem.